THE EFFECT OF FAMILY SUPPORT AND COMPLIANCE IN CONTROL OF LOW-PURINE DIET PATTERNS ON HYPERURICEMIA IN BOJONEGORO BASED ON LAWRENCE GREEN'S THEORY - Alfina Lutfiati; Evita Muslima Isnanda Putri; Sri Mulyani; Ahmad Mafthukin; Rahmawati (MEDALION Journal: Medical Research, Nursing, Health and Midwife Participation, 2026)
Hyperuricemia is a condition characterized by elevated uric acid levels in the blood, which can cause joint pain and impaired activity in the elderly. Adherence to a low-purine diet and family support are important factors in preventing hyperuricemia. This study aimed to analyze the effect of family support and adherence to a low-purine diet on hyperuricemia based on Lawrence Green's theory. This study used a quantitative correlational design with a cross-sectional approach. The study sample consisted of 48 elderly people aged ≥ 60 years at the Elderly Posyandu in Tlatah Village, Purwosari District, Bojonegoro Regency, selected using a simple random sampling technique. The independent variables were family support and adherence to a low-purine diet, while the dependent variable was hyperuricemia. Data collection used questionnaires and uric acid examination observation sheets. Data analysis used a logistic regression test with a significance level of α <0.05. The results showed that the family support variable had a significant p value of 0.020 (<0.05), which means there is an effect of family support on hyperuricemia in the elderly. The Exp(B) value of 0.134 indicates that elderly people with good family support have a lower chance of experiencing hyperuricemia. The low-purine diet adherence variable showed a significant p value of 0.002 (<0.05), which means there is an effect of low-purine diet adherence on hyperuricemia in the elderly. The Exp (B) value of 0.061 indicates that elderly people who adhere to a low-purine diet have a lower risk of hyperuricemia. The conclusion of this study is that family support and adherence to a low-purine diet influence the incidence of hyperuricemia in elderly people. Good family support and adherence to a low-purine diet can help reduce the risk of hyperuricemia in elderly people